Modeling Intraindividual Variability in Growth with Measurement Burst Designs. Issue 1 (2nd January 2021) - Nestler, Steffen
ABSTRACT: Technical advancements have made it easier for researchers to conduct studies in which single-measure panel studies are combined with experience sampling studies. This measurement burst design allows applied researchers to answer a number of interesting questions, such as whether the relationships between variables change over bursts. Here we suggest a heterogeneous variability growth model that researchers can use to examine growth across mean levels and across intraindividual variability. Furthermore, interindividual differences in the two types of growth and their relations can be investigated. After introducing the model, we show how the model's parameters can be estimated with a Maximum Likelihood estimator and a Bayesian approach. Furthermore, we illustrate the approach using both fictitious and real data examples and we present the results of a simulation study.